2022
DOI: 10.1097/meg.0000000000002420
|View full text |Cite
|
Sign up to set email alerts
|

Illness stigma, body image dissatisfaction, thwarted belongingness and depressive symptoms in youth with inflammatory bowel disease

Abstract: Background Elevated depressive symptoms are observed in a significant number of youth with inflammatory bowel disease (IBD) and have been linked to illness stigma and social isolation. Body image dissatisfaction is an understudied variable in the pediatric IBD literature that may be related to both stigma and social difficulties. It is suspected that, due to the stigmatizing nature of IBD, some youth may feel self-conscious about their body image, which contributes to decreased feelings of social belongingness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The existing body image dissatisfaction literature within IBD has largely focused on adults, finding that greater body image dissatisfaction is associated with identifying as female, greater disease activity, and elevated psychosocial concerns 4,6 . Studies with pediatric samples have similarly found that body image dissatisfaction is associated with female sex, older age at diagnosis and assessment, greater body mass index (BMI), more active disease, greater illness stigma, and more depression and anxiety 8,9 . Our cross‐sectional work used a body image‐specific questionnaire and found that increased dissatisfaction was associated with older age and greater patient‐reported disease symptoms but, notably, depressive symptoms were the only significantly associated psychosocial factor within a regression model 10 .…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The existing body image dissatisfaction literature within IBD has largely focused on adults, finding that greater body image dissatisfaction is associated with identifying as female, greater disease activity, and elevated psychosocial concerns 4,6 . Studies with pediatric samples have similarly found that body image dissatisfaction is associated with female sex, older age at diagnosis and assessment, greater body mass index (BMI), more active disease, greater illness stigma, and more depression and anxiety 8,9 . Our cross‐sectional work used a body image‐specific questionnaire and found that increased dissatisfaction was associated with older age and greater patient‐reported disease symptoms but, notably, depressive symptoms were the only significantly associated psychosocial factor within a regression model 10 .…”
Section: Introductionmentioning
confidence: 78%
“…4,6 Studies with pediatric samples have similarly found that body image dissatisfaction is associated with female sex, older age at diagnosis and assessment, greater body mass index (BMI), more active disease, greater illness stigma, and more depression and anxiety. 8,9 Our cross-sectional work used a body image-specific questionnaire and found that increased dissatisfaction was associated with older age and greater patient-reported disease symptoms but, notably, depressive symptoms were the only significantly associated psychosocial factor within a regression model. 10 However, the cross-sectional literature has precluded determining if and how dissatisfaction with one's body changes over time, and whether depressive symptoms are related to changes.…”
Section: Abstract Body Image Concerns Crohn's Disease Depression Pedi...mentioning
confidence: 96%
“…Research also shows a strong link between body image concerns and PD in individuals coping with a variety of chronic illnesses, such as fibromyalgia (Berk et al, 2020 ; Geller et al, 2022 ), endometriosis (Geller et al, 2021 ; Sullivan-Myers et al, 2023 ), IBD (McDermott et al, 2015 ; Roberts et al, 2022 ; Wabich et al, 2020 ), breast cancer (Campbell-Enns & Woodgate, 2015 ; Trindade et al, 2018 ), type 1 diabetes (Salah et al, 2022 ), psoriasis (Gündüz et al, 2020 ), and systemic lupus erythematosus (Rodrigues et al, 2021 ). Building on these findings and informed by research that connects body image in IBS with health-related quality of life (Jones et al, 2006 ; Kopczyńska et al, 2018 ), we propose that the increased risk of PD in patients with IBS could be partially attributed to a decline in their quality of life due to heightened body dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Second, thwarted belongingness is positively correlated with depression. 46 When a person is deprived of a sense of belonging, it may lead to elevated levels of stress, anxiety, depression, and other negative emotions. Previous studies have found that a sense of belonging plays a role in how interpersonal relationships influence individual mental health.…”
mentioning
confidence: 99%